Bragg Resonance around the Coast of Hardwall - Noviantri, Viska; Rachmawati, Ro?fah Nur (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Basically, when waves pass an uneven basis, then this wave will be split into transmission and reflection waves. First of all, it will be shown that a sinusoidal seabed can lead to the phenomenon of Bragg resonance. Bragg resonance occurs when the wave-length comes at twice the wave-length of a sinusoidal basis. The method used to obtain approximation solution is a multi-scale asymptotic expansion method. A research on the effect of Bragg resonance on sinusoidal basis had been studied. Sinusoidal basis can reduce the amplitude of the incoming wave so that the amplitude of the wave transmission is quite small. In these researcher, the coast is assumed ideal and can absorb all the energy of the wave transmission. If the beach can reflect waves, this indicates that the existence of sinusoidal basis is more harmful to the coast. This mechanism relies on the distance between the base sinusoidal and beaches. The present research will examined the influence of the base, when there was a beach of hard-wall on the right, which was perfectly capable of reflecting waves. Having regard to the phase difference, from super positioned waves when they hit the beach, so it can determine the safert and the most dangerous distance.